2010
DOI: 10.1158/1535-7163.mct-09-0650
|View full text |Cite
|
Sign up to set email alerts
|

ALK1-Fc Inhibits Multiple Mediators of Angiogenesis and Suppresses Tumor Growth

Abstract: Activin receptor-like kinase-1 (ALK1) is a type I, endothelial cell-specific member of the transforming growth factor-β superfamily of receptors known to play an essential role in modulating angiogenesis and vessel maintenance. In the present study, we sought to examine the angiogenic and tumorigenic effects mediated upon the inhibition of ALK1 signaling using a soluble chimeric protein (ALK1-Fc). Of 29 transforming growth factor-β-related ligands screened by surface plasmon resonance, only bone morphogenetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
156
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(165 citation statements)
references
References 34 publications
(59 reference statements)
8
156
0
Order By: Relevance
“…As indicated in the Introduction, both a ligand trap, the ALK1-Fc (18), and the anti-hALK1 antibody are currently being tested in clinical trials as antiangiogenesis agents. The biggest difference between these two approaches is that the ligand trap will scavenge all ALK1 ligands, thereby also preventing the binding of BMP9 to other receptors, which could ultimately lead to stimulation of angiogenesis by also inhibiting the antiangiogenic activity of BMP9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in the Introduction, both a ligand trap, the ALK1-Fc (18), and the anti-hALK1 antibody are currently being tested in clinical trials as antiangiogenesis agents. The biggest difference between these two approaches is that the ligand trap will scavenge all ALK1 ligands, thereby also preventing the binding of BMP9 to other receptors, which could ultimately lead to stimulation of angiogenesis by also inhibiting the antiangiogenic activity of BMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical phase I studies are currently being carried out with ALK1-Fc, a soluble chimeric protein consisting of the extracellular part of ALK1 fused to a Fc fragment (39) (ClinicalTrials.gov Identifier NCT 00996957). In mice that were orthotopically implanted with metastatic breast cancer cells (MCF7), ALK1-Fc treatment led to a 70% reduction in tumor burden (18). In the RIP1-Tag2 model for pancreatic cancer, which is highly dependent on the angiogenic switch in the tumors in a specific stage, it was shown that treatment with ALK1-Fc reduced tumor growth and progression due to reduced tumor angiogenesis.…”
mentioning
confidence: 99%
“…Dalantercept and its murine version, RAP-041, bind with high affinity to BMP9 and BMP10, thereby inhibiting activation of endogenous ALK1 (27). In preclinical models, RAP-041 inhibits maturation of vascular endothelial cells, disrupts vascular development, and displays potent antitumor activity accompanied by decreased tumor vascularity (24,27).…”
Section: Introductionmentioning
confidence: 99%
“…Dalantercept and its murine version, RAP-041, bind with high affinity to BMP9 and BMP10, thereby inhibiting activation of endogenous ALK1 (27). In preclinical models, RAP-041 inhibits maturation of vascular endothelial cells, disrupts vascular development, and displays potent antitumor activity accompanied by decreased tumor vascularity (24,27). Most notably, RAP-041 inhibits tumor angiogenesis and tumor growth in the RIP1-Tag2 murine model, similar in effect to reduced ALK1 gene dosage (24), and inhibits both vascularity and growth of breast cancer in an orthotopic tumor model (27).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent data support the opposite function for BMP9. Inhibition of ALK1 activity both by pharmacologic and genetic approaches inhibits angiogenesis in a mouse model of multistep tumorigenesis, therefore inhibition of the ALK1/BMP9 system impairs tumor growth and progression [151,152]. Consistent with these data, an ALK1-Fc-fusion protein that acts as a ligand trap for BMP9 is in clinical trial, and is expected to diminish angiogenesis and proliferation of solid tumors [143,153].…”
Section: Bmps In Liver Carcinogenesismentioning
confidence: 80%